Comparing Three Varieties of Labisia pumila (Primulaceae): Phytochemicals and Antioxidation - Chua, Lee Suan; Abdullah, Farah Izana; Mohd Salleh, Faezah (Trends in Sciences, 2022)
Labisia pumila is a traditional medicinal herb that is widely used by women to firm the uterus after childbirth. Recent scientific studies have also proven its pharmacological importance. However, the comparison of phytochemicals in the different varieties of the herb is very limited in literature. Therefore, 3 common varieties of L. pumila leaves were extracted in a reflux system, and consequently the crude extract was fractionated using reversed phase solid phase extraction (SPE) into individual fractions according to solvent polarity. L. pumila var. alata (LPA) showed the highest yield of crude extract and total phenolics content which was also in line with high DPPH radical scavenging activity. While, L. pumila var. pumila with red leaves (LPPR) exhibited higher total flavonoids and triterpenoids than its green leaves counterpart (LPPG). Higher antioxidant capacity was possibly due to the presence of plant co-pigments in LPPR. Glycosylated flavones including orientin were putatively detected in the intermediate polar fraction of LPA based on mass fragments. However, 0 % methanol (polar) and 100 % methanol (less polar) fractions notably contained compounds competing oxygen with nitric oxide radicals from the formation of nitrite ions. Proton NMR spectral analysis proposed N-[1-(2,3-dihydro-1,4-benzodioxin-6-yl)-1-hydroxy-3-(morpholin-4-yl)propan-2-yl]decanamide and 4-[({1,3-bis[(2-ethylpenta-3,4-dien-1-yl)oxy]propan-2-yl}oxy)methyl]hexa-1,2-diene in the 0 % methanol and 100 % methanol fractions, respectively. This study concluded that the plant variety of alata was more antioxidative than pumila. The detection of orientin and its derivatives are first time reported in LPA. Glycosylated flavones are more likely to be hydrogen atom and/or electron donors contributing to the major antioxidant property of the herb. HIGHLIGHTS pumila var. alata (LPA) and L. pumila var. pumila (LPP) are two commonly used varieties LPA showed to have higher phenolics, but LPP had higher flavonoids and terpenoids content LPA exhibited higher antioxidant capacity because of higher phenolics content Many glycosylated flavones, especially orientin found in 50 % methanol fraction of LPA HPLC, tandem mass spectrometry and proton NMR discovered new phytochemicals in LPA GRAPHICAL ABSTRACT